Water use three rice flooding management systems under Mediterranean climatic conditions - Aguilar, M.=700 1 Borjas, F.
(Es, En)
ilus., 20 ref.
Keywords: ORYZA SATIVA; RIEGO; DOSIS DE RIEGO; CRECIMIENTO; RENDIMIENTO; COSTOS; USO DEL AGUA; ESPAÑA